Hepatocellular carcinoma: preoperative gadoxetic acid-enhanced MR imaging can predict early recurrence after curative resection using image features and texture analysis. - Ahn, Su Joa; Kim, Jung Hoon; Park, Sang Joon; Kim, Seung Tack; Han, Joon Koo (Abdominal Radiology, 2019)
Purpose: To investigate whether pre-operative gadoxetic acid-enhanced MRI can predict early recurrence after curative resection of single HCC using image features and texture analysis.Materials and methods: 179 patients with single HCC and who underwent pre-operative MRI were included. Two reviewers analyzed MR findings, including the tumor margin, peritumoral enhancement, peritumoral hypointensity on the hepatobiliary phase (HBP), diffusion restriction, capsule, tumoral fat, washout, portal-vein thrombus, signal intensity on HBP, and satellite nodule. Texture analysis on the HBP was also quantified. A multivariate analysis was used to identify predictive factors for early recurrence, microvascular invasion (MVI), and the tumor grade.Results: For early recurrence, satellite nodule, peritumoral hypointensity, absence of capsule, and GLCM ASM were predictors (P < 0.05). For MVI, satellite nodule, peritumoral hypointensity, washout, and sphericity were predictors (P < 0.05). Satellite nodules, peritumoral hypointensity, diffusion restriction, and iso to high signal intensity on HBP were predictor for higher tumor grade (P < 0.05). Satellite nodules and peritumoral hypointensity were important showed common predictors for early recurrence, MVI, and grade (P < 0.05). The sensitivity and specificity for satellite nodule were 47.36% and 96.25%. When added texture variables to MRI findings, the diagnostic performance for predicting early recurrence is improved from 0.7 (SD 0.604-0.790) to 0.83 (SD 0.787-0.894).Conclusion: MR finding, including satellite nodule and peritumoral hypointensity on the HBP, as well as the texture parameters are useful to predict not only early recurrence, but also MVI and higher grade.